2011
DOI: 10.1536/ihj.52.353
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Evaluation of Fibrillation Cycle Length Predicts the Efficacy of Bepridil for Interruption of Long-Lasting Persistent Atrial Fibrillation

Abstract: SummaryAlthough bepridil is effective for conversion of long-lasting persistent atrial fibrillation (AF) to sinus rhythm, it sometimes takes a long time to interrupt AF and there is no feasible index to predict its efficacy.In 60 patients with long-lasting persistent AF, bepridil (100-200 mg/day) was administered and continued for 8 weeks while body surface ECG was recorded every 2 weeks. The fibrillation cycle length (FCL) was evaluated using the spectral analysis of the fibrillation waves in each ECG. AF was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Similarly, 53 % of the 60 patients with long-lasting persistent AF were converted to SR by bepridil (100-200 mg/day for 8 weeks). Comparing these responders and non-responders revealed that the only difference was that the prolongation of fibrillation CL became significantly larger in responders suggesting that repetitive evaluation of fibrillation CL can be a feasible index to predict the efficacy of bepridil therapy [378]. Another study showed the same results (conversion in 50 % of the patients by 200 mg/day bepridil) and reached the same conclusion regarding responders [379].…”
Section: Human Data On Hemodynamic Effects Of Monatepilmentioning
confidence: 60%
“…Similarly, 53 % of the 60 patients with long-lasting persistent AF were converted to SR by bepridil (100-200 mg/day for 8 weeks). Comparing these responders and non-responders revealed that the only difference was that the prolongation of fibrillation CL became significantly larger in responders suggesting that repetitive evaluation of fibrillation CL can be a feasible index to predict the efficacy of bepridil therapy [378]. Another study showed the same results (conversion in 50 % of the patients by 200 mg/day bepridil) and reached the same conclusion regarding responders [379].…”
Section: Human Data On Hemodynamic Effects Of Monatepilmentioning
confidence: 60%
“…7 We have previously reported that PAF tended be associated with longer FCL than persistent AF, but such a distinction still carries considerable error when using FCL as the only predicting index. 8 In the present study, we hypothesized that a combination of clinical parameters including FCL could distinguish PAF and non-PAF with acceptable sensitivity and specificity. The aim of this study was therefore to establish a scoring system for the distinction of PAF and non-PAF in patients with first documented AF.…”
mentioning
confidence: 94%
“…Measuring the ECG-derived atrial fibrillatory rate (AFR) is a noninvasive method and has been used to study the electrical remodeling that occurs during AF. [6][7][8] Furthermore, it has been proposed that AFR can be used to assess antiarrhythmic drug effects [9][10][11][12] and may predict the likelihood of druginduced cardioversion. 7 The alterations in atrial activity evident on the surface ECG following administration of a number of antiarrhythmic drugs (including dofetilide and ranolazine) have been studied, 9,10,[13][14][15] yet no such studies on the use of combination therapies are available.…”
Section: Introductionmentioning
confidence: 99%